220k views
4 votes
place the following steps in order to complete the square and solve for the quadratic equation, x squared -6x +7=0

User Anvay
by
5.7k points

2 Answers

6 votes

Answer:

F,A,D,C,E,B

Explanation:

I had this problem on algebra nation and got it right

User Cyndia
by
5.9k points
1 vote
To solve the quadratic by complete square method we proceed as follows:
x²-6x+7=0
this can be written as:
x²-6x=-7
but
c=(-b/2a)^2
c=(-(-6)/2)^2=9
next we add 9 on both sides of our expression to get:
x²-6x+9=-7+9
x²-6x+9=2
factoring out the LHS we get:
(x-3)(x-3)=2
(x-3)²=2
getting the square root of both sides we obtain:
x-3=+/-√2
hence:
x=3+/-√2
User James Campbell
by
6.6k points